Pemantauan Konsumsi Air Pada Prototipe Gedung Tiga Lantai Berbasis Internet of Things - Achmad Fauzan, Bagas Dwi Atmaja; Utomo, Eko Budi; Purnomo, Didik Setyo (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2025)
Monitoring water consumption with the Internet of Things (IoT) is a significant innovation in improving water utilization efficiency in multi-story buildings. This research develops a monitoring system on a three-story building prototype, which combines the MQTT protocol, the Node-Red visualization platform, and two sensors: the YF-B6 and the analog water flow meter sensor. The YF-B6 sensor measures the number of pulses from the water flow to determine the volume, flow rate, and velocity of the water, while the analog water flow meter sensor is integrated with the ESP32-CAM module to capture images of the water flow indicator and process them into volume values using image processing. Data from both sensors are sent to the cloud MQTT broker and visualized interactively through the Node-Red dashboard. This system is implemented on a three-story building prototype to replicate the distribution and monitoring of water usage on each floor. The research results indicate that this system can provide water consumption data with an error percentage of 0.2% and an absolute error of 0.03 m³. This system will also be used for the industrial automation workshop learning module to introduce the Internet of Things (IoT) in an educational environment.